FASILITASI IMPLEMENTASI NEW POSYANDU 6 SPM: ADMINISTRASI POSYANDU DALAM PELAYANAN DAN TATA KELOLA KELEMBAGAAN - Rokhayati (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2025)
Background:. The transformation of primary health care services is one of the key pillars in Indonesia's Health System Transformation agenda to support the national vision of “Indonesia Emas 2045.” As the frontline of community-based services at the village level, Posyandu has evolved into the New Posyandu 6 SPM, expanding its service coverage to include education, health, public works, housing, public order and safety, and social welfare. This role expansion presents new challenges in administrative management and institutional governance. To address these challenges, a facilitation program was conducted in Ngalang Village, Gunungkidul Regency, aiming to enhance the capacity of Posyandu supervisors, administrators, and cadres.Objective: This activity aimed to strengthen the capacity of the Posyandu supervisory team, administrators, and cadres in understanding and implementing administrative procedures and institutional governance of the Posyandu 6 SPM model. Methods:The facilitation activity was conducted using interactive lectures, question-and-answer sessions, and guided discussions, supported by PowerPoint presentations.Results: The facilitation was conducted over two days in Ngalang Village and involved 85 participants, including Posyandu supervisory teams, administrators, and cadres. The activity was participatory and engaging. Evaluation results showed an improvement in participants' knowledge and skills in designing administrative and institutional governance frameworks for the Posyandu.Keyword: Posyandu 6 SPM, Service Administration, Institutional Governance